Crescimento pró-pobre no Brasil : impactos regionais - França, João Mário Santos de (2010)
This research was presented as a completion work for a PhD degree in Economics and brings together three papers in the area of growth. The first of them, uses the methodology developed by Kakwani, Khabdker and Son (2004) to analyze the existence of growth "pro-poor" in regions of Brazil from 1995 to 2005. We used as a support poverty measures: P(0), P(1) and P(2) and the GINI index. The results show that such policies have caused the greatest impact in the southern and southeastern of Brazil. The second paper develops three econometric models in Panel Data to calculate the income-poverty elasticity and inequality-poverty elasticity for geographic regions of Brazil, in a disaggregated way. For the estimations we used as measures the proportion of poor, the poverty gap and poverty gap squared. As was observed that the inequality-poverty elasticity is greater than the growth-poverty elasticity, the reduction in inequality measured by the GINI index is more sensitive to inequality rate’s falls than to the average income’s increments. At last, but not least, the third paper uses the methodology developed by Kraay (2004) to analyze the importance of each component of the growth “pro-poor” for the states of the regions of Brazil. In the northeast region the shifts in income have be en more significant in explaining the pro-poor growth when compared to inequality decreases. In the southeast region the lessening of inequality seems even more meaningful when compared to the northeast region.